Does the method of botulinum neurotoxin injection for limb spasticity affect outcomes? A systematic review. (June 2017) - Chan, Aaron K; Finlayson, Heather; Mills, Patricia B
Objective: To systematically review randomized controlled trials of botulinum neurotoxin for limb spasticity to determine whether different injection techniques affect spasticity outcomes. Methods: MEDLINE, EMBASE, CINAHL, and Cochrane Central Register of Controlled Trials electronic databases were searched for English language human randomized controlled trials from 1990 to 13 May 2016. Studies were assessed in duplicate for data extraction and risk of bias using the Physiotherapy Evidence Database scale and graded according to Sackett's levels of evidence. Results: Nine of 347 studies screened met selection criteria. Four categories of botulinum neurotoxin injection techniques were identified: (1) injection localization technique; (2) injection site selection; (3) injectate volume; (4) injection volume and site selection. There is level 1 evidence that: ultrasound, electromyography, and electrostimulation are superior to manual needle placement; endplate injections improve outcomes vs. multisite quadrant injections; motor point injections are equivalent to multisite injections; high volume injections are similar to low volume injections; and high volume injections distant from the endplate are more efficacious than low volumes closer to the endplate. Conclusion: Level 1 evidence exists for differences in treatment outcomes using specific botulinum neurotoxin injection techniques. Findings are based on single studies that require independent replication and further study.